Genetic Material Upgrading: Misconception Identification Study in High School Biology Teachers - Ika Sukmawati; Karunia Galih Permadani (Universitas Tidar, 2020)
This study aims to identify and map patterns of genetic misconceptions in high school biology teachers. This research was conducted in several stages, including the development of diagnostic test instrument with Certainty of Response Index (CRI). The instrument used in measuring misconceptions in this study is a three-tier test diagnostic instrument. There are 20 questions covering Basic Competencies 3.3, 3.5, 3.6, 3.7, and 3.8. The cognitive level of the questions covers C2 to C5 in Bloom Taxonomy. The validator's assessment shows that the instrument is suitable for data collection. The results of data collection indicate that the topics identified as having misconceptions among high school teachers are quite high (above 50%), among others: (1) The relationship between DNA, genes, and chromosomes; (2) Chromosome structure of eukaryotic cells; (3) The process of protein synthesis (transcription, translation, and genetic code); (4) Mendel Law 1; (5) Mendel Law 2; (6) Crossing-Over, Sex-Linkage, and Non-Disjunction; and (7) Causes of Mutations. Apart from misconception data, this study also reveals the experiences of teachers in conducting Biology teaching and learning activities, especially related to Genetics in high school.